2010
DOI: 10.1161/circheartfailure.109.877720
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Heart Rate Recovery and Chronotropic Incompetence in Patients With Heart Failure With Preserved Ejection Fraction

Abstract: Background-This study assessed the chronotropic response to exercise and heart rate (HR) recovery after exercise in a carefully phenotyped group of patients with heart failure with preserved left ventricular ejection fraction (HfpEF) and a control group of similar age and gender distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 39 publications
6
131
1
6
Order By: Relevance
“…Phan et al [8] found that 34% of patients with HFpEF have CI during maximal exercise when defined by %Max PHR and 63% when defined by %HRR. In order to avoid age, functional capacity and resting HR biases of each individual [1,4,5,[20][21][22][23][24], for comparison analysis of patient data we have used %HRR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phan et al [8] found that 34% of patients with HFpEF have CI during maximal exercise when defined by %Max PHR and 63% when defined by %HRR. In order to avoid age, functional capacity and resting HR biases of each individual [1,4,5,[20][21][22][23][24], for comparison analysis of patient data we have used %HRR.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have revealed the existence of depresssed chronotropic reserve in patients with HFpEF even compared with older, age-matched controls and independent of rate-slowing medication use. [7][8][9][10][11]30] Similar to CHF, this is likely to be related to downstream deficits in beta-adrenergic stimulation and/or autonomic dysfunction. [7,8] Data on the relation between the extent of diastolic dysfunction and CI in patients with HFpEF are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32) In HFpEF, baroreflex sensitivity is reduced and impaired heart rate recovery. 33,34) Patients with HFpEF have multiple arteriosclerotic risk factors, and stiffened arterial walls in the baroreceptor regions impair baroreflex function.…”
Section: 14-17)mentioning
confidence: 99%
“…Beta-blockers inconsistentlyinverse these modifications, contracting sympathetic drive and proliferating β-receptor susceptibility. Up-to-the minute HF with conserved LVEF (HFpEF), [19,20] plasma catecholamine concentrations are not elevated; however, even in the lack of epicardial coronary artery disease HFpEF patients do not generally have an increase in EF in reaction to exercise or β-adrenergic stimulation, [20] symptomatic of β-adrenergic receptor desensitization [21].…”
Section: Introductionmentioning
confidence: 99%